CORRELATION AND PATH COEFFICIENT ANALYSIS OF SOME GROWTH AND YIELD CONTRIBUTING TRAITS IN COWPEA (VIGNA UNGUICULATA (L) WALP.) EXPOSED TO ALPHA-SPIN NANO PARTICLES (FULafia Journal of Science and Technology, 2019)
A field experiment was conducted in the Research and Experimental Fields of the Botanical Garden of Federal University Lafia,  Nasarawa State to estimate correlation and path co-efficient analysis on growth and yield traits in cowpea exposed to alpha spin nanoparticles. Nine advanced cowpea lines sourced from Institute of Agricultural Research, Samaru, Zaria and one from Nasarawa State Agricultural Programme, Lafia, were sown in a Randomized Complete Block Design in three replications and evaluated for nine morphological and reproductive traits namely vine length, number of leaves, leave area, number of branches, number of pods perplant, pod length, number of seeds per pod, 100 seed weight and seed yield per plant. Among the studied yield contributing traits, number of pod per plant (0.618), number of seed per pod (0.443), pod length (0.698),100 seed weight(0.818) and number of branches (0.403) showed significant correlation coefficient to yield per plant. 100 seed weight showed highest direct effect (p=0.850) to yield followed by number of seed per pod (p=0.807). The number of leaves showed highest indirect effect to yield through number of branches (p=0.147), followed by vine length through number of leaves (p=0.116).The first three Principal Components (PCs)accounted for 81.1% of the total variation implying their high selection stability. This character association study helps to know the contribution of the different characters to total yield; this information helps breeders to improve the yield directly or indirectly by improving yield contributing traits.